Human Resource Management System - Bandara P.M.G.R.I; Kumarasiri R.D.S.R; Silva H.C.M; Herath A.M.T.N; D.I. De Silva; Dulanji Cooray (International Journal of Engineering and Management Research, 2022)
The main focus of the essay, "Human Resources Management System," is on controlling the administrator of a company's human resources department. The systems and procedures at the intersection of human resources and management are referred to as a human resource management system (HRMS).technology (IT) with human resources management (HRM). It combines HRM as a discipline, especially its fundamental HR actions and procedures related to information technology, as opposed to data processing programming. Systems developed into enterprise resource planning (ERP) software packages and established procedures. This paper's major goal is to make it easier for the administrator to keep track of everyday activities including attendance, projects, work, appointments, etc. This essay discusses the steps involved in identifying the personnel, tracking their hourly attendance, and figuring out their actual payable hours or days. This document should keep track of every employee's time spent working for the firm so that it may be used to evaluate performance. Based on that, transfers, dismissals, and promotions are possible.